Theoretical aspects of forming the team activity of architectural organizations - Khymytsia, Olha (Видавництво Львівської політехніки, 2019)
In the paper, the theoretical aspects of the formation teamwork of architectural organizations.
Keywords: teamwork; architectural organization; team; practical psychology; communication